What do Preschool Teachers' Professional Biographies Reveal about Interweaving of Profession and Creativity? - Tina Štemberger; Majda Cencič (University of Maribor Press, 2015)
In the field of research in creativity, some dilemmas regarding methodological approaches have arisen. Consequently, a shift from the traditional, psychometric approach to a more qualitative approach has been in progress recently. The so-called life history research is a type of qualitative research, which, in the field of educational research, focuses on teachers and preschool teachers, on their perspective of work and life; it can be a sort of a personal reflection. In the paper, we present the process and the results of such research, which included preschool teachers who had been identified as creative. The aim of the research was to establish how preschool teachers define and experience the interweaving of their own profession and creativity. The results of qualitative analysis thus show some of the key factors of preschool teachers' creative career.